(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
RA Al-Asror is an early childhood education institution located on Jl. Legoksari Raya No. 1c, Patemon Village, Gunung Pati District, Semarang City, Central Java Province. In the health sector, the lack of health promotion in PAUD institutions causes children not to understand the importance of a clean and healthy lifestyle. This service aims to provide children with information about how to care for clean nails and how to wash hands properly and correctly. The method used in community service activities is in the form of counseling (socialization). The result of the activity is an increase in students’ understanding of fingernails and hand hygiene so that they are expected to pay more attention to and maintain their own health to avoid various diseases.